Ecological Role of A Softcoral-Associated Bacterium Arthrobacter sp. on Marine Biofilm-Forming Bacteria - OCKY KARNA RADJASA; AGUS SABDONO (Microbiology Indonesia, 2008)
A marine bacterium species associated with softcoral Sinularia sp. collected from vicinity of Peucang island, Ujung Kulon, West Java, was successfully screened for estimating its ecological role through inhibiting marine biofilm-forming bacteria isolated from the surrounding colonies of Sinularia sp. and was identified as closely related to Arthrobacter nicotianae based on its 16S rDNA structure. The bacterium was found to inhibit the growth of four biofilm-forming isolates (Vibrio harveyi, V. fortis, Staphylococcus sciuri, and Tenacibaculum marilutum) indicating the significance of secondary metabolite production which may provide important defensive functions against fouling microorganisms. The isolate was capable of amplifying gene fragments of non-ribosomal peptide synthetases. A 416 bp long DNA fragment was obtained and the deduced amino acid sequence showed conserved signature regions for the peptide synthetases and revealed a high similarity to that of Actinoplanes teichomyceticus (62.5% identity).